Decreased expression of RASSF10 correlates with poor prognosis in patients with colorectal cancer. Issue 42 (October 2017) - Ma, Junxun; Zhang, Sujie; Hu, Yi; Li, Xiaoyan; Yuan, Fang; Sun, Danyang; Wang, Lijie; Zhang, Fan; Chen, Guangying; Cui, Pengfei
Abstract : Abstract: Ras association domain protein 10 ( RASSF10 ) was reported to act as a prognostic indicator in various types of cancer and it was proved to be tumor suppressor gene in colorectal cancer (CRC). The purpose of this study was to evaluate the prognostic significance of RASSF10 in CRC. Quantitative real-time polymerase chain reaction was used to detect the messenger RNA (mRNA) expression while enzyme-linked immunosorbent assay was taken to measure the protein expression of RASSF10 in tumor tissues and adjacent normal tissues from 102 patients with CRC. The relationship between RASSF10 expression level and clinical characteristics of CRC patients was analyzed by chi-squared test. In addition, the association between overall survival of CRC patients and RASSF10 expression was estimated by Kaplan–Meier analysis. Cox regression analysis was used to evaluate the prognostic value of RASSF10 . The expression level of RASSF10 in tumor tissues was significantly lower than that in the normal tissues both at mRNA and protein levels. Moreover, the expression level was correlated with lymph-node-metastasis and tumor-node-metastasis stage. Kaplan–Meier analysis suggested that patients with high expression level of RASSF10 had a longer overall survival than those with low level (log-rank test, P  < .001). Besides, RASSF10 might be a potential biomarker in the prognosis of CRC according to cox regression analysis. The down regulated of RASSF10 is found in CRC and it may be an ideal prognostic marker.